Request modifications by Malay speakers of English in the workplace: A contrastive pragmatic analysis - Idris, Aizatul Aisyah Mohd; Ismail, Isma Noornisa (Universitas Syiah Kuala, 2023)
A request is one of the most frequently used speech acts in a persons daily life. Many studies have been conducted on the act of request and several researchers have developed strategies and modifications that are used in delivering requests to mitigate the imposition of the FTA. Thus, this study aims to investigate the internal and external modifications applied in requests by Malay speakers of English and Malay to specific requestees in the workplace context following Blum-Kulka et al.s (1989) Request Modification framework. To achieve the purpose of this study, a qualitative approach was employed. A number of 30 Malay workers were asked to complete a Written Discourse Completion Task (WDCT) which involves eliciting requests. The findings revealed that the respondents used more internal modifications in their requests with people of equal relative power compared to high and low relative power, and used more external modifications in requests with a higher degree of imposition in certain contexts. This implies the act of request from the viewpoint of the Malaysian workplace context. It offers meaningful insight into the preferences of working Malay speakers of English in modifying their requests, and shows the level of pragmatic competence of Malay speakers of English and Malay in the workplace environment.